ME AND MY BESTIE FOR LIFE - Idowu, Babatunde Michel; Dinne, Chinedu Ernest; Ogbu, Daniel Chinazam (ESUT JOURNAL OF SOCIAL SCIENCES, 2026)
This study, situated within the frameworks of differential association and social learning theories, delved into the nexus between peer influence and substance abuse amongst Nigerian undergraduate students. Focusing on Alex Ekwueme Federal University, Ndufu-Alike Ikwo (AE-FUNAI), and a survey design was employed. A representative sample of 392 students were drawn, ensuring statistical validity. Data collection utilised a validated 26-item questionnaire meticulously reviewed by the research supervisor. Descriptive statistical analyses, encompassing frequencies, percentages, and means, illuminated the key findings. The study examined three research objectives, which are to examine the common types of substance abused by AE-FUNAI undergraduate students; to document the relationship between peer influence and substance abuse among undergraduate students; and lastly, to investigate the consequences of substance abuse among AE-FUNAI undergraduate students. Firstly, a statistically significant relationship between peer influence and substance abuse among AE-FUNAI undergraduates was unveiled. Cannabis, alcohol, heroin, ecstasy, tobacco, inhalants, and prescription medications emerged as the most commonly abused substances. Furthermore, the detrimental consequences of substance abuse were laid bare, impacting academic performance, raising the risk of criminal activity, jeopardising health, and straining relationships with family, friends, and romantic partners. Mental health concerns were also identified as a potential consequence. The study concluded that peer influence causes AEFUNAI undergraduate students to engage in substance abuse. Also shown the grave danger of substance abuse on academic and health status of users. To combat this concerning trend, the study advocates for a multi-pronged approach. First, educational campaigns are crucial to raising awareness of the dangers associated with substance abuse. Secondly, establishing readily accessible support services for struggling students is paramount. Finally, enacting and rigorously enforcing stringent anti-substance abuse policies within AE-FUNAI would serve as a potent deterrent.